THE EFFECTIVENESS OF POWER TEACHING TECHNIQUE TO TEACH SPEAKING VIEWED FROM STUDENTS’ SELF-ACTUALIZATION - Yuniasih, Eka (Jurnal Pedagogy, 2016)
The objectives of the research was finding out whether: (1) Power Teaching Technique is more effective than Drilling Technique to teach speaking at the Eleventh Graders of SMA N 1 Metro; (2)the students having high self-actualization have better speaking skill than those having low self-actualization; and (3) there is an interaction between teaching techniques and students’ self-actualization in teaching speaking. The method which was applied in this research was experimental study. It was conducted at the eleventh graders of SMA N 1 Metro. It consists of 11 classes, the total number of population is 325 students. The sample of the research were two classes. The sampling technique used was cluster random sampling. Each class was divided into two groups (the students having low and high self-actualization). The data were analyzed by using ANOVA 2 x 2 and Tukey test. The data analysis shows the following findings: (1) Power Teaching Technique is more effective than Drilling Technique in teaching speakingto the eleventh graders of SMAN 1 Metro; (2) the students having high self-actualization have better speaking skill than those having low self-actualization; and (3) there is an interaction between teaching techniques and students self-actualization in teaching speaking. It can be concluded that Power Teaching Technique is an effective technique to teach speaking at the eleventh graders of SMA N 1 Metro.